Pendidikan Gizi dalam Upaya Pencegahan Obesitas pada Mahasiswa dan Siswa Melalui Kader Generasi Z - Septa Indra Puspikawati; Susy Katikana Sebayang; Shelviana Mathofani (Media Gizi Kesmas, 2024)
Background: In 2016, over 1.9 billion adults aged 18 years and over were overweight. Of this number, more than 650 million are obese. Over 340 million children and adolescents aged 5-19 years were overweight or obese in 2016. Obesity hurts public health, especially adolescents. Objectives: This research aims to increase knowledge related to nutrition, especially obesity and health screening Methods: This activity was carried out at Airlangga University in Banyuwangi on May 27, 2023, with the schedule of events including morning exercise, nutrition education, and anthropometric and health examinations. The targets for this activity are students at SMAN 1 Glagah and SMAN 1 Giri and students at Airlangga University in Banyuwangi and STIKES Banyuwangi. Results: Research results show an increase in knowledge of 14.3. Most of >55% of respondents had normal BMI, abdominal circumference, blood pressure, and blood sugar. Conclusions: Nutrition education related to obesity for pupils and students has been proven to increase knowledge related to nutrition and obesity.